Acute diverticulitis: Key features for guiding clinical management. Issue 128 (July 2020) - Sugi, Mark D.; Sun, Derek C.; Menias, Christine O.; Prabhu, Vinay; Choi, Hailey H.
Highlights: Acute colonic diverticulitis is a common cause of emergency department visits. Complications of diverticulitis include abscess, fistula, and peritonitis. Abscesses less than 3 cm may not require percutaneous drainage or surgery. Fistulae to the bladder and pelvic organs are often underrecognized acutely. Differentiating chronic diverticulitis from cancer remains a diagnostic challenge. Abstract: Diverticular disease of the colon and small bowel is an important cause of pathology leading to emergency department visits and urgent gastrointestinal surgery. CT is a highly sensitive and specific modality for the diagnosis of acute diverticulitis and its complications as well as for the exclusion of alternate causes of pathology. Ultrasound, MRI and virtual CT colonoscopy have important adjunct roles for screening and workup of complications in specific patient populations. While diverticular disease most commonly involves the descending and sigmoid colon, it can also affect the proximal colon and small bowel. Acute diverticulitis may be categorized as uncomplicated or complicated according to the degree of inflammatory changes and related complications it induces, although some degree of overlap exists in clinical practice. Uncomplicated diverticulitis is classically characterized by localized inflammation surrounding a diverticulum ranging from wall thickening and phlegmonous change to the development of small, localized pericolic abscesses. Complicated forms of disease manifest with larger pericolic and distant abscesses, fistulae to adjacent organs, perforation, and peritonitis. Recurrent episodes of diverticulitis may lead to muscular hypertrophy of the bowel wall and luminal narrowing, potentially leading to bowel obstruction. Several imaging features may help to differentiate diverticulitis from colonic malignancy, however this remains a diagnostic imaging challenge that often requires further evaluation with colonoscopy. In this review, we discuss the pathophysiology and key imaging features of acute diverticulitis and its complications. We explore both common and uncommon presentations of the disease involving the colon and small bowel, acute and chronic manifestations of disease, and pitfalls to recognize when imaging alone may be insufficient to distinguish benign from malignant.